Der Raumordnerische Vertrag als Instrument zur Absicherung von Kooperationen im zentralörtlichen System - Greiving, Habil Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
The article considers the question to what extent co-operations can strengthen the central place system as a concept of spatial planning. The legitimacy of the central place system as part of classical spatial planning that acts in a sovereign way is questioned. Here the focus is put on the application of the principle of functionality instead of the conventional principle of territoriality in the allocation of central place functions. The policy impacts of urban associations and shared central places that have been tested in spatial planning practice in this respect suffer from the lack of a binding agreement on the distribution of functions. In this context the author introduces the spatial planning contract as a possible solution and discusses it using the example of the Dessau area.